Tyrosine kinase Pyk2 is involved in colonic smooth muscle contraction via the RhoA/ROCK pathway - Tong, L; Ao, J-P; Lu, H-L; Huang, X; Zang, J-Y; Liu, S-H; Song, N-N; Huang, S-Q; Lu, C; Chen, J; Xu, W-X (Physiological research, 2019)
The contraction of gastrointestinal (GI) smooth muscles is regulated by both Ca(2+)-dependent and Ca(2+) sensitization mechanisms. Proline-rich tyrosine kinase 2 (Pyk2) is involved in the depolarization-induced contraction of vascular smooth muscle via a Ca(2+) sensitization pathway. However, the role of Pyk2 in GI smooth muscle contraction is unclear. The spontaneous contraction of colonic smooth muscle was measured by using isometric force transducers. Protein and phosphorylation levels were determined by using western blotting. Pyk2 protein was expressed in colonic tissue, and spontaneous colonic contractions were inhibited by PF-431396, a Pyk2 inhibitor, in the presence of tetrodotoxin (TTX). In cultured colonic smooth muscle cells (CSMCs), PF-431396 decreased the levels of myosin light chain (MLC20) phosphorylated at Ser19 and ROCK2 protein expression, but myosin light chain kinase (MLCK) expression was not altered. However, Y-27632, a Rho kinase inhibitor, increased phosphorylation of Pyk2 at Tyr402 and concomitantly decreased ROCK2 levels; the expression of MLCK in CSMCs did not change. The expression of P(Tyr402)-Pyk2 and ROCK2 was increased when CSMCs were treated with Ach. Pyk2 is involved in the process of colonic smooth muscle contraction through the RhoA/ROCK pathway. These pathways may provide very important targets for investigating GI motility disorders.
Keywords: fokální adhezní kinasa 2; kolon; Male; orgánové kultury - kultivační techniky; rhoA GTP-Binding Protein; signální transdukce; buněčné kultury; rho GTP-Binding Proteins; mužské pohlaví; Enzyme Inhibitors; Organ Culture Techniques; Rho proteiny vázající GTP; rhoA protein vázající GTP; Signal Transduction; Focal Adhesion Kinase 2; Mice, Inbred ICR; kinázy asociované s Rho; Animals; zvířata; Colon; Cell Culture Techniques; myši; myši inbrední ICR; hladké svalstvo; Muscle Contraction; rho-Associated Kinases; Muscle, Smooth; svalová kontrakce; Mice; inhibitory enzymů